Barriers to Intercultural Communication of the Nias Tribe (Study in Penyengat Village, Sungai Apit District, Siak Regency) - Imron Adrian; Tessa Shasrini (LPPM Institut Studi Islam Sunan Doe, 2023)
This study aims to find out what are the barriers to intercultural communication in the Nias Tribe Society (Study in Penyengat Village, Sungai Apit District, Siak Regency). This study used a qualitative method by conducting interviews and observations of six research subject informants with different cultural backgrounds. This study uses the theory of accommodation which explains how the two different cultures can adjust to one another starting from behavior when interacting with one another and can reduce conflict or disagreement when talking to one another. The results of this study explain what are the obstacles to intercultural communication between the Nias people and the people of Penyengat Village, namely the barriers (language, perception, experience, nonverbal, culture and prejudice) from the languages of the two cultures, both of them do not understand Indonesian. and with wrong mention/delivery or body language, negative Prejudice Barriers arise. and differences of opinion in different tribes can cause communication barriers, adjusting to social life in a new environment. fear that results in prejudice against different cultures, especially the people of Penyengat Village have a fear of the Nias Tribe Causing Problems in Penyengat Village.